Sustainable Tuna Fishing in Small Island Developing States: Governance and Policies in the Kiribati Islands. - Asa, Semo (Auckland University of Technology, 2025)
The sustainable governance of marine resources in Small Island Developing States (SIDS) such as the Kiribati Islands sits at the intersection of ecological stewardship, postcolonial sovereignty, and global socio-economic interdependency. My study explores the transnational governance of sustainable tuna fishing in Kiribati with one of the largest and most biodiverse tuna fish stocks in the world. In Kiribati, tuna is not merely a tradable commodity; it represents a cultural lifeline, economically, and politically amid shifting climate frontiers and volatile international markets. Positioned within the blue economy as a governance-sustainability nexus, my study advances an inquiry that foregrounds transnational governance as both a site of contestation and a coordination platform. Through a critical case study method drawing on secondary data (and some feedback from a few experts), my research examines how Kiribati’s tuna fisheries are governed across a diverse ecosystem of state, market, and civil society actors, each advancing diverging conceptions of what constitutes sustainable tuna fishing. By operationalising 15 Regulatory Standard-Setting (RSS) schemes and evaluating them through a Governance Triangle Framework, my research probes how these transnational mechanisms align or fail to align with Kiribati’s sustainability priorities and national sovereignty claims. The evaluation of the 15 RSS schemes’ effectiveness is anchored in five governance drivers articulated by Haas et al. (2022): legal enforceability, effectiveness and adaptability, credibility, inclusiveness, and empowerment. Recognising persistent asymmetries and inequities in how power is exercised across governance regimes, I further propose a sixth governance principle – “Equity and Justice” to address the often-underrepresented social equity dimensions within existing frameworks. The analysis is further guided by the normative objectives set forth in the United Nations Sustainable Development Goals (UN SDGs), in particular UN SDG #13 (Climate Action), UN SDG #14 (Life Below Water), and UN SDG #17 (Partnerships for the Goals). These global commitments offer an analytical compass through which the governance of Kiribati’s tuna fisheries can be understood not only as a local or regional issue but as a matter of global strategy and transnational governance. The findings suggest that the effectiveness of transnational RSS schemes in Kiribati fisheries is uneven, constrained by fragmented authority structures, limited national capacity, and underlying structural dependencies. However, the study also highlights opportunities for adaptive, inclusive, and cooperative governance pathways that centre the voices of SIDS within the broader international business and ocean governance discourses. In doing so, my study contributes to closing what may be termed a “blue deficit” in the International Business (IB) literature, a long-standing oversight in how ocean spaces and their governance have been conceptualised, particularly within the IB literature and global strategy. By re-framing Kiribati’s tuna fisheries as both a governance challenge and a site of strategic agency, I hope my study brings renewed attention to how SIDS engage with the contested spaces of ocean governance and offers practical IB policy insights that may support a sustainable future within the Pacific blue economy.
Keywords: Transnational governance; Global strategy; Sustainable tuna fishing; Kiribati islands; The Pacific blue economy